1997
DOI: 10.1088/0022-3727/30/11/001
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoretic separation of nano-particles

Abstract: Abstract. We show for the first time that it is possible to separate a population of nanoparticles into two subpopulations solely on the basis of their dielectric properties. Using nanofabricated electrode arrays it has been shown that a solution of 93 nm diameter latex beads with a distribution of surface charge can be separated by the application of non-uniform AC electric fields (dielectrophoresis). The mixture separated into two populations, one experiencing positive dielectrophoresis and the other negativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
142
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(145 citation statements)
references
References 13 publications
(14 reference statements)
2
142
0
1
Order By: Relevance
“…Eq. (7) is manifestly in the self-adjoint (Sturm-Liouville) form and the reciprocity theorem follows directly [5].…”
Section: Analytical Methodologymentioning
confidence: 97%
See 3 more Smart Citations
“…Eq. (7) is manifestly in the self-adjoint (Sturm-Liouville) form and the reciprocity theorem follows directly [5].…”
Section: Analytical Methodologymentioning
confidence: 97%
“…[5,7,8]. For simplicity of the analysis, the authors consider the charge carrier transport to be onedimensional along a linear coordinate x, and the injected minority carrier densities to be small compared to the majority carrier densities, i.e., low injection assumption.…”
Section: Analytical Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…Such systems are capable of providing high electric fields with small applied voltages. It has been shown that a wide range of particles such as cells, latex spheres, and microorganisms can be selectively manipulated using dieleetrophoretic techniques [1][2][3] and more recently, sub-micrometre particles sueh as latex spheres, maeromoleeules, DNA and viruses have been manipulated and charaeterised [4][5][6][7][8][9][10]. For sub-mierometre particles it was believed Brownian motion would prevent deterministic movement by DEP, but this premise has been disproved.…”
Section: Introductionmentioning
confidence: 99%